Shortage of essential pediatric medications puts children's health at risk. Results from a European Confederation of Primary Care Paediatricians (ECPCP) Survey 2023 - Christine Magendie; Gottfried Huss; Laura Reali; Stephen Reingold (Elsevier, 2024)
Unparalleled drug shortages during the winter of 2022/2023 had a profound impact on paediatric primary care across Europe. A survey conducted by the European Confederation of Primary Care Paediatricians (ECPCP) evaluated the availability of essential pediatric drugs and the resulting challenges. The survey was conducted between January and March 2023 and included responses from 640 paediatricians from 18 countries. The results of the survey indicated that there were substantial shortages, particularly of child friendly formulations of commonly prescribed medicines. Paediatricians in the survey feared that the use of less appropriate alternatives could potentially compromise the efficacy and safety of treatment. The survey findings highlight the urgent need for coordinated actions at multiple levels to ensure the availability of essential pediatric medications and safeguard children's health in future crises.